Strategies and creativity used by fansubbers in subtitling 'Hot and Young Seoul Trip X NCT Life' to overcome language barriers (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
This research focuses on the subtitling strategies and creative subtitling used in translating the Korean variety show Hot and Young Seoul Trip X NCT LIFE (2018) into Indonesian and the impact of fan subtitles to overcome language barriers. In order to draw more understanding, qualitative content analysis was applied to describe the subtitling strategies and creative subtitling used by the fansubbers in producing Indonesian subtitles. An online survey was conducted to determine the impact of the subtitling from the fans' perspective. The research findings on subtitling strategies were obtained from 1599 data and showed that there were eight strategies applied in this research. Amid those strategies, transfer with 1434 data found is the most used strategy, followed by imitation, dislocation, expansion, paraphrase, transcription, condensation, and deletion. Then, the creative subtitling used in the work using different colors, fonts, and punctuation that is influenced by field (topic), tenor (relationship), and mode (circumstances). The online survey results prescribe that the subtitles of the fan help the audience overcome language barriers by producing translated audiovisual content into their language. Therefore, the fansubbers' decision to combine subtitling strategies and creative subtitling helps the foreign audiences overcome language barriers